The Spread of Information and Interaction on Social Media in Influencing Information Asymmetry and Investment Decision-Making - Harry Hidayat Kamil (CERED Indonesia Institute, 2025)
This study examines the influence of social media in Indonesia on investment decision-making. Currently, social media platforms are developing rapidly and have become an important source of information for investors. This can be observed through the emergence of corporate social media accounts, investment company social media platforms, and stock analyst social media accounts across various platforms. These channels aim to provide diverse information to assist investors in making informed investment decisions. This research explains how information dissemination and user interactions on social media, which generate a wisdom of crowds effect, can reduce information asymmetry in the investment decision-making process. The study employs primary data collected by distributing questionnaires to investment-related social media groups and communities. A total of 150 respondents were selected using purposive sampling. The findings illustrate how information disseminated through corporate social media, investment company social media, and stock analyst social media influences information asymmetry in investment decision-making. Furthermore, the study describes how interactions among social media users (wisdom of crowds) within these platforms contribute to reducing information asymmetry and shaping investment decisions.